2012
DOI: 10.3126/jnbs.v7i1.6411
|View full text |Cite
|
Sign up to set email alerts
|

Consequence of Gender and Job Characteristics with Normative Commitment

Abstract: Keywords: organizational commitment, personal/job characteristics, normative commitment BackgroundOrganizational commitment means employees, loyalty and willingness to contribute to the organization. Employee commitment is of great importance; because high levels of commitment lead to several favorable organizational outcomes. It is possible to be dissatisfied with a particular feature of a job while retaining a reasonably high level of commitment to the organization as a whole. When creating a commitment stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The positive effect of task significance on organizational commitment; job performance; quality of work life, job satisfaction has been identified (Sadono, 2016;Allan, Duffy & Collisson, 2016;Hassan & Samah n.d.;Ali et al, 2014;Umukoro & Egwakhe, 2019). Another job characteristic dimension autonomy increases job satisfaction of employees, increases employee commitment; vitality of employees (Shrestha, 2010;Ali Job Characteristics andOrganizational Committment 43 et al, 2014, Sadono, 2016;Sisodia& Das, 2013;Naqvi, Ishtiaq, Kanwal & Ali, 2013;Taghavi & Gholami, 2015;Lin & Ping, 2016;Ozturk et al, 2014;Tummers, Steijan, Nevicka & Heerema, 2018;Umukoro & Egwakhe, 2019). The feedback dimension is important for the employees to continuously improve their job performance and many studies have identified the positive effect of feedback on organizational commitment; (Ozturk et al, 2014;Farazi et al, 2015;Umukoro & Egwakhe, 2019;Amakiri & Luke, 2016;Volmer, Spurk & Niessen, 2012).…”
Section: Job Characteristics and Organizational Commitmentmentioning
confidence: 99%
“…The positive effect of task significance on organizational commitment; job performance; quality of work life, job satisfaction has been identified (Sadono, 2016;Allan, Duffy & Collisson, 2016;Hassan & Samah n.d.;Ali et al, 2014;Umukoro & Egwakhe, 2019). Another job characteristic dimension autonomy increases job satisfaction of employees, increases employee commitment; vitality of employees (Shrestha, 2010;Ali Job Characteristics andOrganizational Committment 43 et al, 2014, Sadono, 2016;Sisodia& Das, 2013;Naqvi, Ishtiaq, Kanwal & Ali, 2013;Taghavi & Gholami, 2015;Lin & Ping, 2016;Ozturk et al, 2014;Tummers, Steijan, Nevicka & Heerema, 2018;Umukoro & Egwakhe, 2019). The feedback dimension is important for the employees to continuously improve their job performance and many studies have identified the positive effect of feedback on organizational commitment; (Ozturk et al, 2014;Farazi et al, 2015;Umukoro & Egwakhe, 2019;Amakiri & Luke, 2016;Volmer, Spurk & Niessen, 2012).…”
Section: Job Characteristics and Organizational Commitmentmentioning
confidence: 99%